A Method to Noninvasively Identify Cardiac Bioelectrical Sources. Issue 8 (20th March 2014) - SOHN, KWANGHYUN; LV, WENER; LEE, KICHANG; GALEA, ANNA; HIRSCHMAN, GORDON; BARRETT, CONOR; COHEN, RICHARD J.; ARMOUNDAS, ANTONIS A.
<x xml:space="preserve">Abstract</x> Background We have introduced a method to guide radiofrequency catheter ablation (RCA) procedures that estimates the location of a catheter tip used to pace the ventricles and the target site for ablation using the single equivalent moving dipole (SEMD). Objective To investigate the accuracy of this method in resolving epicardial and endocardial electrical sources. Methods Two electrode arrays, each of nine pacing electrodes at known distances from each other, sutured on the left‐ and right‐ventricular (LV and RV) epicardial surfaces of swine, were used to pace the heart at multiple rates, while body surface potentials from 64 sites were recorded and used to estimate the SEMD location. A similar approach was followed for pacing from catheters in the LV and RV. Results The overall (RV & LV) error in estimating the interelectrode distance of adjacent epicardial electrodes was 0.38 ± 0.45 cm. The overall endocardial (RV & LV) interelectrode distance error, was 0.44 ± 0.26 cm. Heart rate did not significantly affect the error of the estimated SEMD location (P > 0.05). The guiding process error became progressively smaller as the SEMD approached an epicardial target site and close to the target, the overall absolute error was ∼0.28 cm. The estimated epicardial SEMD locations preserved their topology in image space with respect to their corresponding physical location of the epicardial electrodes. Conclusion The proposed algorithm suggests one can efficiently and accurately resolve epicardial electrical sources without the need of an imaging modality. In addition, the error in resolving these sources is sufficient to guide RCA procedures.